Musculoskeletal consultations from childhood to adulthood: a longitudinal study. (28th November 2019) - Prathivadi Bhayankaram, N; Lacey, R J; Barnett, L A; Jordan, K P; Dunn, K M
Abstract: Background: The Global Burden of Disease reports indicate that musculoskeletal conditions are important causes of disability worldwide. Such conditions may originate in childhood, but studies investigating changes longitudinally and from childhood to adulthood are infrequent. Methods: Nine birth cohorts of children (starting at ages 7–15 years) were followed. Participants were identified from Consultations in Primary Care Archive, an electronic health record database of 11 English general practices. Musculoskeletal consultation prevalence figures were calculated, and reasons for consultation evaluated. Results: Annual musculoskeletal consultation prevalence was similar across cohorts for each age. Prevalence increased from 6 to 16% between ages 7 and 22 and was higher in males until age 15, after which prevalence was higher in females. Pain was the most common reason for consultation. Back pain consultations increased from 1 consultation/1000 7 year olds to 84 consultations/1000 22 year olds. Lower limb pain consultations increased from 21 consultations/1000 7 year olds to 56 consultations/1000 22 year olds. Conclusions: This study shows that from childhood, individuals are more likely to seek healthcare for musculoskeletal consultations as they age, but rates are not increasing over time. Changes in consultation rates by age, gender and pain region may inform studies on the development of chronic musculoskeletal pain over the life-course.